Butterflies (Lepidoptera: Papilionoidea and Hesperioidea) from Serra da Jibóia, Bahia State, Brazil - Zacca, Thamara; Bravo, Freddy; Araújo, Maíra Xavier (EntomoBrasilis, 2011)
A list of species of butterflies from Serra da Jibóia, a mountainous massif in the Recôncavo of Bahia State, is presented based on specimens deposited in the entomological collection Prof. Johann Becker of Museu de Zoologia da Universidade Estadual de Feira de Santana (MZUEFS), results that should contribute with the increment of biodiversity knowledge of the butterfly fauna of the State. The list includes 140 species, 86 of which are new records to Bahia and a new species of genus of Perophthalma Westwood (Riodinidae). Nymphalidae was the richest family with 60 species. Most of the species listed in the present work has a widely geographic distribution in Brazil and occur in open areas. Borboletas (Lepidoptera: Papilionoidea e Hesperioidea) da Serra da Jibóia, Bahia, Brasil Resumo. Uma lista das espécies de borboletas da Serra da Jibóia, um maciço montanhoso no Recôncavo baiano, é apresentada com base no exame da coleção entomológica Prof. Johann Becker do Museu de Zoologia da Universidade Estadual de Feira de Santana (MZUEFS), visando contribuir para o conhecimento da fauna de borboletas do estado da Bahia. A lista inclui 140 espécies, das quais 86 espécies são novos registros para o estado da Bahia e uma nova espécie do gênero of Perophthalma Westwood (Riodinidae). Nymphalidae foi a família de maior riqueza com 60 espécies. A maioria das espécies listadas possui ampla distribuição geográfica no Brasil e ocorre em áreas abertas.